Determination of Substance P by capillary zone electrophoresis in rat brain - Babu, CVS; Han, KY; Kim, Y; Yoo, YS (ELSEVIER SCIENCE BV, 2003)
In the complex neuronal network, chemical messengers like neuropeptides play a key role in signaling. To understand the mechanism of signaling, it is necessary to analyze the levels of neuropeptides. from biological sources, which is important for neuroscience research. In the present work, a detailed investigation of the capillary zone electrophoresis (CZE) method was carried out to detect and quantify Substance P (SP), a bioactive neuropeptide, in rat brain tissues. The method involves specifically, a combination of solid phase extraction and immunoprecipitation prior to the CZE quantification. In this procedure, antibodies are used to capture the analyte of interest before the separation by CZE. Different separation parameters like buffer type, concentration, pH and applied voltage were the steps taken to study and achieve high efficiency CZE separation. CZE analysis was performed in an untreated fused-silica capillary column (35 cmx75 mum i.d.) and 185 nm wavelength using 100 mM phosphate buffer (pH 2.5) as a separation buffer. Electrophoresis in acidic mode and successive washing procedures solved the adsorption problem. The method provides a rapid analysis time of less than 15 min with 3.91% of RSD. Simultaneously, SP was quantified by Matrix Assisted Laser Desorption Ionization-Time of Flight-Mass Spectrometry (MALDI-TOF-MS) and compared with CZE data. Starting from milligram amounts of brain tissue, the method allowed the detection of low picomole amounts of SP and the combined use of CZE and MALDI-TOF-MS was a success in quantification in this study. (C) 2003 Elsevier Science B.V. All rights reserved.
Keywords: LASER-DESORPTION/IONIZATION-TIME; FLIGHT MASS-SPECTROMETRY; ALZHEIMERS-DISEASE; SEPARATION; IMMUNOREACTIVITY; NEUROPEPTIDES; PEPTIDES; PROTEIN; PLASMA